A hydroxyl-modified porous coordination polymer material, preparation method and sulfur dioxide capture application

By designing and synthesizing a double-ligand cage-based porous coordination polymer material PCN-2OH, and using a hydroxyl-modified pore structure, the existing flue gas desulfurization technology has solved the problems of high energy consumption and high solid waste, achieving high efficiency and selection. Effective adsorption of SO2.

CN119119508BActive Publication Date: 2025-01-21DEZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411620617.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-21
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing flue gas desulfurization technology generates a large amount of solid waste and has high energy consumption, making it difficult to effectively remove low concentrations of SO2.

Method used

By designing and synthesizing a double-ligand cage-based porous coordination polymer material PCN-2OH, the hydroxyl-modified pore structure is used to adjust the pore window size to achieve efficient and selective adsorption of SO2.

Benefits of technology

It achieves efficient and selective adsorption of SO2, reduces energy consumption and the generation of solid waste, and has the potential to be developed as an SO2 adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119508B_ABST
    Figure CN119119508B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation and adsorption separation of crystalline porous materials, and relates to a hydroxyl-modified porous coordination polymer material, a preparation method and sulfur dioxide capture application. The chemical formula is [Ni3(OH)(TMBTTP)(BDC‑2OH)3], and the porous coordination polymer has two types of cages, cylindrical and spindle-shaped. The permanent pores and suitable pore size and hydroxyl-modified pore environment can provide sufficient space and abundant hydrogen bonding sites for gas molecule adsorption, making the porous coordination polymer material suitable for SO2 adsorption separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and adsorption separation of crystalline porous materials, and relates to a hydroxyl-modified porous coordination polymer material, a preparation method and sulfur dioxide capture application. Background Art

[0002] my country has abundant coal reserves, and coal will continue to play an important role in my country's energy supply now and in the future. The exhaust gas produced by coal powder combustion contains 10-12% CO 2 and 500~3000 ppm SO 2 . Among them SO 2 It is a toxic and corrosive gas that will pose a major threat to human health and the environment. Currently, although flue gas desulfurization technology can remove most of SO from flue gas, 2 Dry, regenerable sorbent selectively captures SO under ambient conditions 2 It has attracted increasing interest and is considered to be a good method for removing low concentration SO 2 Compared with flue gas desulfurization, this method has the advantages of low energy consumption and reduced solid waste. In addition, the recovered SO 2 Can be used to produce valuable chemicals such as sulfuric acid.

[0003] Porous coordination polymer (PCN) materials are crystalline porous materials assembled from metal nodes and organic molecules. Due to their high porosity, structural diversity and highly customizable pore functions, they have attracted a lot of attention in gas adsorption and are considered to be solid adsorbents with great practical prospects. For PCN materials used to effectively adsorb low-concentration gases, pore size adjustment and specific functional group modification are effective design and synthesis schemes. Summary of the invention

[0004] For SO 2 The size and chemical properties of the molecule are determined by the design and synthesis strategy of the dual-ligand cage-based PCN. By modifying the hydroxyl groups on the ligands, not only adsorption functional sites are provided in the PCN pores, but also the window size of the pores is adjusted to achieve efficient and selective adsorption of SO 2 The prepared materials were systematically characterized by single crystal X-ray diffraction, gas adsorption and fixed bed mixed gas penetration testing, and their structure, pore properties and SO 2 The actual capture performance is analyzed by combining theoretical calculations with the adsorption mechanism. The PCN-2OH material provided by the present invention has the potential to be developed into SO 2 Potential of adsorbents.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first object of the present invention is to provide a hydroxyl-modified porous coordination polymer material, the chemical formula of which is [Ni 3 (OH)(TMBTTP)(BDC-2OH) 3 ], where TMBTTP is an organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (CAS No.: 2027486-17-3), H 2 BDC-2OH is 2,5-dihydroxyterephthalic acid (CAS No.: 610-92-4), named PCN-2OH;

[0007] The porous coordination polymer material has a cage-like microporous structure modified with hydroxyl groups.

[0008] Furthermore, from the perspective of framework connection construction, the crystal structure of PCN-2OH belongs to the trigonal system, and the space group is P6 3 / mcm , the unit cell parameters are: a = 16.9485(18) Å, b =16.9485(18) Å, c=15.019(3) Å, α = β= 90 o , γ= 120 o .

[0009] Furthermore, in the porous polymer structure of PCN-2OH, its crystallographic asymmetric structural unit includes 1 Ni(II) ion, 1 / 3 µ 3 -O group, 1 BDC 2− -2OH ligand and 1 / 3 TMBTTP ligand; [Ni 3 (OH)(TMBTTP)(BDC-2OH) 3 ],

[0010] The Ni(II) ion is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2− -2OH ligand carboxyl O atom, 1 µ 3 -O atom and one N atom from the TMBTTP ligand; three adjacent Ni(II) ions are bound by a µ 3 -O group and six different BDCs 2− The six carboxyl groups of the -2OH ligands are bridged to form a typical trinuclear metal cluster [Ni 3 (μ 3 -O)(COO) 6 ]; Each metal cluster and BDC 2−-2OH ligands are connected alternately to form a three-dimensional porous structure with acs topology, and TMBTTP ligands connect [Ni 3 (μ 3 -O)(COO) 6 ] clusters, further dividing them into a three-dimensional framework of PACs topological structure.

[0011] Furthermore, in the PCN-2OH structure, there are two cage structures, spindle-shaped and cylindrical, in which the upper and lower vertices of the spindle cage are composed of one [Ni 3 (μ 3 -OH)(COO) 6 ] clusters, and 3 [Ni 3 (μ 3 -OH)(COO) 6 ] Clusters, vertices and intermediate clusters are connected by BDC 2− -2OH ligands are connected, and the three [Ni 3 (μ 3 -O)(COO) 6 ] The clusters are connected by TMBTTP ligands, and the distance between the vertices of the spindle cage is 14.2 Å, and the distance between the middle position is about 10.4 Å;

[0012] The upper and lower planes of the cylindrical cage contain three [Ni 3 (μ 3 -O)(COO) 6 ] cluster and one TMBTTP ligand, the cylinder wall consists of six BDC 2− -2OH occupies the bottom of the cylindrical cage, and the distances between the upper and lower atoms are 10.4 Å and 5.8 Å, respectively. 2− The -2OH ligands and -OH groups of metal clusters are distributed in the windows and cross-section centers of the two cage structures.

[0013] The present invention also provides a method for preparing the porous coordination polymer material, comprising the following steps:

[0014] Under sealed conditions, organic ligands 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (TMBTTP), 2,5-dihydroxyterephthalic acid (H 2 BDC-2OH and nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) dissolved in N , N- A mixed solution of dimethylacetamide and water, and an appropriate amount of 48 wt % tetrafluoroboric acid aqueous solution was added to adjust the acidity of the solution, and the PCN-2OH metal organic framework crystal material was obtained through a solvothermal reaction.

[0015] Furthermore, the organic ligand H 2 The molar ratio of BDC-2OH, TMBTTP and metal salt is 1:(0.2~0.5):(1~3);

[0016] For every 0.1 mmol of H 2 BDC-2OH corresponds to 1~2.5 ml N , N -dimethylacetamide; for every 0.1 mmol of Ni(NO 3 ) 2 6H 2 O corresponds to 0.1-0.4 ml of deionized water;

[0017] Each 1 ml of DMA corresponds to 15-35 μl of 48 wt% tetrafluoroboric acid aqueous solution. Further, the solvothermal reaction temperature is 95-120° C., and the reaction time is 12-48 hours.

[0018] Furthermore, the porous coordination polymer material is activated by the following method: first, the synthesized material is washed three times with ethanol, and the washed sample is immersed in anhydrous ethanol solution for 24 hours, during which the ethanol is continuously stirred and replaced three times. The sample is filtered to obtain a sample, and then dried in a vacuum oven at 100°C for 4 hours to obtain an activated sample.

[0019] The present invention also provides the porous coordination polymer material in SO 2 Capture application.

[0020] Beneficial technical effects of the present invention: The bifused ring ligand metal organic framework crystal material of the present invention has a novel structure and a stable framework, and there are two types of cages: cylindrical and spindle-shaped. At 77 K, the nitrogen isotherm adsorption curve of PCN-2OH is type I. At a pressure of P / P 0 = 1 is 253.5 cm 3 / g, the specific surface area calculated from the adsorption data is 966 m 2 / g, and the pore size distribution obtained from the adsorption data analysis is 4.7-12.5 Å. This permanent pore channel, suitable pore size, and hydroxyl-modified pore environment can provide sufficient space and abundant hydrogen bonding sites for the adsorption of gas molecules, making this metal-organic framework suitable for SO 2 Adsorption separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1This is a photo of PCN-2OH crystals under a microscope.

[0022] Figure 2 This is a photo of PCN-2OH in powder state.

[0023] Figure 3 Figure 2 shows the coordination environment and coordination mode of the Ni metal center in PCN-2OH.

[0024] Figure 4 This is the three-dimensional framework structure diagram of PCN-2OH.

[0025] Figure 5 Figure 2 is the structural diagram of the spindle-shaped cage in PCN-2OH.

[0026] Figure 6 Figure 2 shows the structure of the cylindrical cage in PCN-2OH.

[0027] Figure 7 The powder X-ray diffraction spectra of synthesized PCN-2OH and its treatment under different conditions.

[0028] Figure 8 This is the thermal gravimetric curve of PCN-2OH.

[0029] Fig. 9 This is the nitrogen adsorption-desorption isotherm of PCN-2OH at 77 K.

[0030] Fig.10 is the SO of PCN-2OH at 298 K 2 / CO 2 / N 2 Comparison of adsorption isotherms.

[0031] Fig.11 is the SO of PCN-2OH at 308 K 2 / CO 2 / N 2 Comparison of adsorption isotherms.

[0032] Fig.12 This is the IAST selectivity curve of PCN-2OH at 298 K.

[0033] Fig.13 PCN-2OH at 25 °C for SO 2 and CO 2 Schematic diagram of the dynamic breakthrough curve.

[0034] Fig.14 PCN-2OH to SO 2 and CO 2 Adsorption heat curve. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0036] Example 1

[0037] Weighing organic ligand H 2 BDC-2OH (0.01 mmol), TMBTTP (0.002 mmol) were dissolved in 0.1 ml DMA by ultrasonication, and metal salt Ni(NO 3 ) 2 6H 2 O (0.01 mmol) was dissolved in 0.02 ml of deionized water, and then 1.5 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added, and the mixture was sealed in a pressure-resistant container, and the metal-organic framework crystal was obtained through a thermal reaction at 85 °C for 48 hours.

[0038] Example 2

[0039] Weighing organic ligand H 2 BDC-2OH (0.02 mmol), TMBTTP (0.005 mmol) were dissolved in 0.5 ml DMA by ultrasonication, and metal salt Ni(NO 3 ) 2 6H 2 O (0.04 mmol) was dissolved in 0.1 ml of deionized water, and then 7.5 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle, and the metal-organic framework crystal was obtained through thermal reaction at 120 °C for 12 hours.

[0040] Example 3

[0041] Weighing organic ligand H 2 BDC-2OH (0.05 mmol), TMBTTP (0.02 mmol) were dissolved in 0.8 ml DMA by ultrasonication, and metal salt Ni(NO 3 ) 2 6H 2 O (0.15 mmol) was dissolved in 0.6 ml of deionized water, and then 20 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle, and the metal-organic framework crystal was obtained through thermal reaction at 100 °C for 36 hours.

[0042] Example 4

[0043] Weighing organic ligand H 2 BDC-2OH (0.1 mmol), TMBTTP (0.02 mmol) were dissolved in 2.0 ml DMA by ultrasonication, and metal salt Ni(NO 3 ) 2 6H 2O (0.3 mmol) was dissolved in 1 ml of deionized water, and then 70 μl of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle, and the metal-organic framework crystal was obtained through thermal reaction at 110 °C for 32 hours.

[0044] The test results of the products obtained in the above embodiments are the same, as shown below:

[0045] (1) Crystal structure determination:

[0046] Single crystals of appropriate size were selected under a microscope, and data were collected on a Bruker SMART APEXII CCD diffractometer. Absorption correction was performed using the SADABS program. SHELXL-2014 was used to solve and refine the structural data for F2 using the direct method and full-matrix least squares method. The crystallographic program used the single-suite Olex2 integrated system. All non-hydrogen atoms were anisotropically refined. The positions and thermal parameters of hydrogen atoms were determined, and the structure was refined by geometric calculations. The contribution of disordered solvent molecules was processed using the SQUEEZE program implemented in PLATON. See the structure diagram. Figure 1-4 The crystallographic data are shown in Table 1.

[0047] Table 1 Crystallographic data of metal organic framework materials

[0048]

[0049] Figure 1 The crystal morphology of PCN-2OH obtained in Example 1-4 under a microscope. Figure 2 The PCN-2OH material obtained in Examples 1-4 is in the form of brown powder. Figure 3 Figure 2 shows the coordination environment and coordination mode of the Ni metal center in PCN-2OH. It can be seen that the Ni(II) ion of PCN-2OH is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2− -2OH ligand carboxyl O atom, water molecule μ 3 -O group and one N atom from the TMBTTP ligand. The four carboxyl O atoms of each dicarboxylic acid are connected to four Ni atoms, all of which are μ 2 -η 1 :η 1 coordination mode.

[0050] Figure 4 The three-dimensional framework structure of PCN-2OH shows that in PCN-2OH, three adjacent Ni(II) ions are separated by 1 μ 3 -O group and six different BDCs 2− The six carboxyl groups of the -2OH ligands are bridged to form a typical trinuclear metal cluster [Ni3 (μ 3 -O)(COO) 6 ]. These trinuclear metal clusters are alternately connected with TMBTTP ligands to form a three-dimensional framework. Figure 5 and Figure 6 The spindle cage and cylindrical cage structures in PCN-2OH are shown in Figure 2, which show that there are two cage structures in the PCN-2OH structure: spindle cage and cylindrical cage. The upper and lower vertices of the spindle cage are composed of 1 [Ni 3 (μ 3 -O)(COO) 6 ] clusters, and 3 [Ni 3 (μ 3 -O)(COO) 6 ] Clusters, vertices and intermediate clusters are connected by BDC 2− -2OH ligands are connected, and the three [Ni 3 (μ 3 -O)(COO) 6 The clusters are connected by TMBTTP ligands. The distance between the vertices of the spindle cage is about 14.2 Å, and the diameter of the middle position is about 10.4 Å. The upper and lower planes of the cylindrical cage contain three [Ni 3 (μ 3 -O)(COO) 6 ] cluster and one TMBTTP ligand, the wall of the cylindrical pore consists of six BDC 2− -2OH occupies the cylindrical cage, with a base diameter and height of 10.4 and 5.8 Å, respectively.

[0051] Figure 7 The X-ray powder diffraction spectrum shows that the prepared PCN-2OH is a pure phase, and its crystal skeleton structure remains unchanged after the sample is activated by ethanol and cycled.

[0052] Figure 8 The thermogravimetric curves show that the thermal stability of the PCN-2OH framework reaches 400 ℃.

[0053] (2) Specific surface area characterization

[0054] Fig. 9 The PCN-2OH framework material of the present invention is P / P 0 = 1 and N at 77 K 2 Adsorption-desorption isotherms. As can be seen from the figure, the saturated N 2 Absorption reaches 253.5 cm 3 / g (STP). By fitting and analyzing the adsorption data, the specific surface area of ​​PCN-2OH was found to be 966 m2 / g, and the pore size distribution is between 4.7 and 12.5 Å.

[0055] (3) Characterization of adsorption and separation performance:

[0056] Fig.10 and Fig.11 The PCN-2OH framework material is at 298 K and 308 K respectively. P / P 0 When SO is 1.0 2 and CO 2 200 mg of the activated adsorbent sample was placed in a vacuum at 120 °C for 3 h. After degassing, the gas adsorption isotherms were tested at 298 K and 308 K. The steam was generated by a high-purity solvent. As can be seen from the figure, under 298 K and 1 bar conditions, the PCN-2OH material has a high adsorption capacity for SO 2 and CO 2 The maximum adsorption capacity was 232.1 cm 3 / g, 63.2 cm 3 / g. At 308K, PCN-2OH crystal material has a strong affinity for SO 2 and CO 2 The maximum adsorption capacity is 189.6 cm 3 / g,50.8cm 3 / g. At 298K and 1 bar, the maximum adsorption difference is 168.9 cm 3 / g, the adsorption difference at P = 0.1 bar reached 48.0 cm 3 / g. These results show that PCN-2OH has a strong 2 and CO 2 The adsorption capacity of SO 2 application potential.

[0057] Fig.12 SO of the PCN-2OH framework material of the present invention 2 / CO 2 IAST selectivity curve of mixed gas at 298 K. The figure shows that under 298 K, PCN-2OH has a higher selectivity to SO 2 / CO 2 The IAST selectivity values ​​ranged from 6.03 to 59.66.

[0058] Fig.13 The separation SO of the PCN-2OH framework material of the present invention 2 / CO 2Breakthrough curve of mixed gas. At 298 K and 1 bar, SO 2 / CO 2 Mixed gas (SO 2 / CO 2 / N 2 , v:v:v=0.2 / 50 / 49.8, SO 2 : 2000 ppm) passed through a quartz tube filled with 0.5 g of PCN-2OH at a flow rate of 100 mL / min. From the breakthrough curve, it can be seen that CO 2 First, it passes through the MOF material, and SO is detected after a certain period of time. 2 Gas molecules. This further demonstrates the good SO 2 The penetration time difference of the mixed gas in PCN-2OH is 35.44 min. The results show that the porous coordination polymer crystal material has the ability to separate SO 2 / CO 2 Potential applications of mixed gases.

[0059] Fig.14 PCN-2OH framework material for SO 2 and CO 2 Adsorption heat curve. In porous coordination polymer crystal materials, SO 2 Q st The value is 59.32 kJ / mol, which is higher than the corresponding CO 2 value, which means that the material has a 2 Compared with CO 2 Have a stronger affinity.

Claims

1. A hydroxyl-modified porous coordination polymer material, characterized in that: The chemical formula is [Ni3(OH)(TMBTTP)(BDC-2OH)3], named PCN-2OH, one of the ligands of PCN-2OH is 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine TMBTTP, and the second ligand is 2,5-dihydroxyterephthalic acid BDC-2OH; The PCN-2OH has a cage-like microporous structure modified with hydroxyl groups; From the perspective of framework connection construction, the crystal structure of PCN-2OH belongs to the trigonal system, and the space group is P6 3 / mcm , the unit cell parameters are: a = 16.9485(18) Å, b =16.9485(18) Å, c=15.019(3) Å, α = β = 90 o , γ = 120 o ; In the porous polymer structure of PCN-2OH, its crystallographic asymmetric structural unit contains 1 Ni(II) ion, 1 / 3 µ3-O group, 1 BDC 2− -2OH ligand and 1 / 3 TMBTTP ligand; [Ni3(OH)(TMBTTP)(BDC-2OH)3], The Ni(II) ion is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2− The carboxyl O atom of the -2OH ligand, one µ3-O atom and one N atom from the TMBTTP ligand; three adjacent Ni(II) ions are bound by a µ3-O group and six different BDCs. 2− The six carboxyl groups of the -2OH ligands are bridged to form a typical trinuclear metal cluster [Ni3(μ3-O)(COO)6]; each metal cluster is connected to the BDC 2− The -2OH ligands are alternately connected to form a three-dimensional porous structure with an acs topological configuration, and the TMBTTP ligands connect the [Ni3(μ3-O)(COO)6] clusters, further dividing them into a three-dimensional framework with a pacs topological structure; In the PCN-2OH structure, there are two cage structures, spindle-shaped and cylindrical. The upper and lower vertices of the spindle cage are occupied by one [Ni3(μ3-OH)(COO)6] cluster respectively, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle. The vertices and the middle clusters are connected by BDC. 2− -2OH ligands, the three [Ni3(μ3-O)(COO)6] clusters in the middle are connected by TMBTTP ligands, and the distance between the vertices of the spindle cage is 14.2 Å, and the distance between the middle position is about 10.4 Å; The upper and lower planes of the cylindrical cage contain three [Ni3(μ3-O)(COO)6] clusters and one TMBTTP ligand, respectively. The wall of the cylinder consists of six BDC 2− -2OH occupies the bottom of the cylindrical cage, and the distances between the upper and lower atoms are 10.4 Å and 5.8 Å, respectively. 2− The -2OH ligands and -OH groups of metal clusters are distributed in the windows and cross-section centers of the two cage structures.

2. A method for preparing a hydroxyl-modified porous coordination polymer material as claimed in claim 1, characterized in that: The following steps are involved: Under sealed conditions, organic ligands 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine TMBTTP, 2,5-dihydroxyterephthalic acid H2BDC-2OH and nickel nitrate hexahydrate Ni(NO3)2·6H2O were dissolved in N , N - A mixed solution of dimethylacetamide and water, and 48 wt % tetrafluoroboric acid aqueous solution was added to adjust the acidity of the solution, and the PCN-2OH metal organic framework crystal material was obtained through a solvothermal reaction.

3. The method for preparing the hydroxyl-modified porous coordination polymer material according to claim 2, characterized in that: The molar ratio of the organic ligand H2BDC-2OH, TMBTTP and nickel nitrate hexahydrate is 1:(0.2-0.5):(1-3).

4. The method for preparing a hydroxyl-modified porous coordination polymer material according to claim 2, characterized in that: Each 0.1 mmol of H2BDC-2OH corresponds to 1~2.5 ml of N , N -dimethylacetamide; 0.1~0.4 ml of deionized water for every 0.1 mmol of Ni(NO3)2·6H2O; N , N -Dimethylacetamide corresponds to 15~35 μl of 48 wt% tetrafluoroboric acid aqueous solution.

5. The method for preparing the hydroxyl-modified porous coordination polymer material according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 95-120° C., and the reaction time is 12-48 hours.

6. Use of the hydroxyl-modified porous coordination polymer material as claimed in claim 1 in SO2 capture.

Citation Information

Patent Citations

  • Double-fused-ring ligand MOF crystal material, preparation method thereof and application of double-fused-ring ligand MOF crystal material in separation of benzene / cyclohexane

    CN118005947A

  • Porous double-fused-ring ligand coordination polymer material, preparation method thereof and application of porous double-fused-ring ligand coordination polymer material in separation of toluene / methylcyclohexane

    CN118063789A